2020
DOI: 10.1111/inr.12643
|View full text |Cite
|
Sign up to set email alerts
|

Unique expatriate factors associated with job dissatisfaction among nurses

Abstract: Aim To assess whether expatriate‐specific factors were associated with nurses’ overall job dissatisfaction after controlling for known factors. Background Current evidence about job dissatisfaction among nurses in Saudi Arabia is not specific to expatriate nurses. Specific aspects such as job insecurity, fear of litigation, and language barriers have not been assessed in the context of job dissatisfaction. Introduction The majority of nurses in the Arab Gulf countries are expatriate. The motive for employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
0
9
0
Order By: Relevance
“… 14 Therefore, not only the barriers to the expatriates but also the job dissatisfaction and turnover are few other issues affecting the nursing sector in Saudi Arabia. 15 , 16 As a result, there is a need to realize and establish strong and effective leadership in the nursing sector in order to handle the challenges and issues and enabling organizational commitment and increasing retention rates, 17 for better managing challenges such as the Covid-19 pandemic. Various studies 15 , 18 , 19 have analyzed nursing retention and linked it with job dissatisfaction, intention to leave, cultural differences, etc., but there is considerably little research focusing on the impact of leadership styles on increasing organizational commitment and retention rates.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Therefore, not only the barriers to the expatriates but also the job dissatisfaction and turnover are few other issues affecting the nursing sector in Saudi Arabia. 15 , 16 As a result, there is a need to realize and establish strong and effective leadership in the nursing sector in order to handle the challenges and issues and enabling organizational commitment and increasing retention rates, 17 for better managing challenges such as the Covid-19 pandemic. Various studies 15 , 18 , 19 have analyzed nursing retention and linked it with job dissatisfaction, intention to leave, cultural differences, etc., but there is considerably little research focusing on the impact of leadership styles on increasing organizational commitment and retention rates.…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction, autonomy of work, and resource adequacy reflected more strong correlations with task, contextual, and adaptive performance; and all types of commitment. As identified in the previous studies (12,14,15,26,38), job satisfaction, one of the important 'quality of work-life' subscale was identified to be significantly influencing job performance and organization loyalty. Thus, it can be analyzed and concluded that quality of work-life can moderately influence the organization loyalty and job performance of the nurses in Saudi Arabia, based on the hypothesis analysis.…”
Section: Discussionmentioning
confidence: 62%
“…Third part of the questionnaire includes 18 items, measured on a 7-point Likert scale ((SD = 0) strongly disagree; (MD = 1) moderately disagree; (LD = 2) slightly disagree; (O = 3) neither disagree nor agree; (LA = 4) slightly agree; (MA = 5) moderately agree; (SA = 6) strongly agree) related to organizational commitment adapted from OCQ. These are further categorized into affective commitment (items 1-6), continuance commitment (items 7-12), and normative commitment (items [13][14][15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations